Issues in Growth of Mathematics Education (Global Journal of Science Frontier Research, 2014)
Mathematics plays an important role in the fast changing educational scenario. It has a wide application in the present growing science and technological world. Mathematical knowledge is the key to understand the science and technology and it can be familiarized through the friendly Mathematical environment among the learners, teachers, parents and other stakeholders from the beginning of schooling. The growth of mathematics education is not satisfactory from the schooling. Due to lack of best practices of the known and unknown factors that to be studied are the hindrances in the growth of mathematics education. This study aims to focus on the issues of the growth of Mathematic education.
Keywords: mathematic education; issues; growth